ELEMENTARY SCHOOL STUDENTS’ CREATIVITY IN EXPLORING TIMBRE THROUGH ENVIRONMENTAL-BASED LEARNING - Utari Dayya Suci Nurani; Resa Respati; Muhammad Rijal Wahid Muharram (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the level of creativity among elementary school students in exploring timbre through environmental-based learning. Creativity in this context encompasses four main aspects: fluency, flexibility, originality, and elaboration. The research employed a quantitative approach with a pre-experimental one-shot case study design, involving 20 second-grade students as participants. The instrument used was a timbre exploration task using objects from the surrounding environment, assessed through a creativity rubric. The results showed that 20% of students demonstrated a high level of creativity, 55% fell into the moderate category, and 25% were in the low category. In the aspect of fluency, more than half of the students showed adequate ability to generate sound variations. However, the aspects of flexibility, originality, and elaboration were still dominated by low to moderate scores, indicating that students had not yet fully developed their ideas in diverse, original, and detailed ways. Environmental-based learning has proven to provide a positive stimulus in fostering students' musical creativity, although further learning strategies are needed to optimize all aspects of creativity. This study recommends the use of contextual approaches and exploratory learning in music education at the elementary school level.